Methodological instructions for independent works in the "Computer circuitry" academic discipline - Skorodielov, Volodymyr Vasyliovych; Lipchanska, Oksana Valentinivna (National technical university "Kharkiv polytechnic institute", 2024)
Computer Circuitry is one of the fundamental disciplines in the field of Computer Engineering. This discipline provides the theoretical and engineering training necessary to perform research and practical work on the research, development and operation of computer hardware, embedded microprocessor and microcontroller systems, computer systems and networks for various purposes (information, medical and industrial). As a result of studying the discipline, students are required to know: the element base of computers (digital integrated circuits of hard and programmable logic with varying degrees of integration), the principles of building on their basis typical functional units of digital devices of computers, microprocessor and microcontroller systems. Students are also required to be able to: analyze and develop schemes of digital functional units and devices of computers based on digital chips of hard and programmable logic; measure parameters, find faults, debug and test digital units and devices, as well as operate them; use technical and reference literature, as well as standards in their development and operation. Students are also required to have practical skills in the development and analysis of computer hardware, microprocessor and microcontroller systems using modern electronic modeling systems. It is obvious that such a large amount of knowledge and skills cannot be mastered without regular and rather intense independent work of students both during classroom works and during independent work at home. Independent work develops the skills of continuous self-improvement and the ability to self-education, intensifies search and research activities and provides an opportunity to acquire the knowledge necessary for practical and scientific activities.
Keywords: methodological instructions; work at lectures; self-check; consultations; methods of control